The Multifaceted Roles of HY5 in Plant Growth and Development - Gangappa, Sreeramaiah N. (2016)
ELONGATED HYPOCOTYL5 (HY5), a member of the bZIP transcription factor family, inhibits hypocotyl growth and lateral root development, and promotes pigment accumulation in a light-dependent manner in Arabidopsis. Recent research on its role in different processes such as hormone, nutrient, abiotic stress (abscisic acid, salt, cold), and reactive oxygen species signaling pathways clearly places HY5 at the center of a transcriptional network hub. HY5 regulates the transcription of a large number of genes by directly binding to cis-regulatory elements. Recently, HY5 has also been shown to activate its own expression under both visible and UV-B light. Moreover, HY5 acts as a signal that moves from shoot to root to promote nitrate uptake and root growth. Here, we review recent advances on HY5 research in diverse aspects of plant development and highlight still open questions that need to be addressed in the near future for a complete understanding of its function in plant signaling and beyond.